Preoperative prevalence of deep vein thrombosis in patients scheduled to have surgery for degenerative musculoskeletal disorders - Keigo Sato (BMC Musculoskeletal Disorders, 2021)
Abstract Background Although the incidence of symptomatic pulmonary thromboembolism after elective surgery for degenerative musculoskeletal disorders is comparatively low, it is extremely detrimental to both patients and health-care providers. Therefore, its prevention is mandatory. We aimed to perform a cross-sectional analysis of deep venous thrombosis (DVT) before elective surgery for degenerative musculoskeletal disorders, including total knee arthroplasty (TKA), total hip arthroplasty (THA), and spinal surgery, and identify the factors associated with the incidence of preoperative DVT. Methods The clinical data of patients aged ≥ 30 years who underwent TKA or THA, and spine surgery for lumbar or cervical degenerative disorders at our institution were retrospectively collected. D-dimer levels were measured preoperatively in all the patients scheduled for surgery. For the patients with D-dimer levels ≥ 1 µg/mL or who were determined by their physicians to be at high risk of DVT, the lower extremity vein was preoperatively examined for DVT on ultrasonography. Results Overall, we retrospectively evaluated 1236 consecutive patients, including 701 men and 535 women. Of the patients, 431 and 805 had D-dimer levels ≥ 1 and < 1 µg/mL, respectively. Of 683 patients who underwent lower extremity ultrasonography, 92 had proximal (n = 7) and distal types (n = 85) of DVT. The preoperative prevalence of DVT was 7.4 %. No patient had the incidence of postoperative symptomatic venous thromboembolism. A multivariate analysis revealed that age ≥ 80 years (odds ratio [OR], 95 % confidence interval [CI]: 2.8, 1.1–7.3), knee surgery (2.1, 1.1–4.0), American Society of Anesthesiologists (ASA) grade 2 (2.8, 1.2–6.8), ASA grades 3 or 4 (3.1, 1.0–9.4), and malignancy (1.9, 1.1–3.2) were significantly associated with DVT incidence. Conclusions This is the first study to conduct a cross-sectional analysis of preoperative DVT data of patients scheduled for elective surgery for degenerative musculoskeletal disorders. Although whether screening for preoperative DVT is needed to prevent postoperative symptomatic pulmonary thromboembolism remains to be clarified, our data suggested that DVT should be noted before surgery in the patients with advanced age, knee surgery, high ASA physical status, and malignancy.